Search for Novel Candidate Mutations for Metronidazole Resistance in Helicobacter pylori Using Next-Generation Sequencing - Binh, Tran Thanh (Antimicrob Agents Chemother, 2015)
Metronidazole resistance is a key factor associated with Helicobacter pylori treatment failure. Although this resistance is mainly associated with mutations in the rdxA and frxA genes, the question of whether metronidazole resistance is caused by the inactivation of frxA alone is still debated. Furthermore, it is unclear whether there are other mutations involved in addition to the two genes that are associated with resistance. A metronidazole-resistant strain was cultured from the metronidazole-susceptible H. pylori strain 26695-1 by exposure to low concentrations of metronidazole. The genome sequences of both susceptible and resistant H. pylori strains were determined by Illumina next-generation sequencing, from which putative candidate resistance mutations were identified. Natural transformation was used to introduce PCR products containing candidate mutations into the susceptible parent strain 26695-1, and the metronidazole MIC was determined for each strain. Mutations in frxA (hp0642), rdxA (hp0954), and rpsU (hp0562) were confirmed by the Sanger method. The mutated sequence in rdxA was successfully transformed into strain 26695-1, and the transformants showed resistance to metronidazole. The transformants containing a single mutation in rdxA showed a low MIC (16 mg/liter), while those containing mutations in both rdxA and frxA showed a higher MIC (48 mg/liter). No transformants containing a single mutation in frxA or rpsU were obtained. Next-generation sequencing was used to identify mutations related to drug resistance. We confirmed that the mutations in rdxA are mainly associated with metronidazole resistance, and mutations in frxA are able to enhance H. pylori resistance only in the presence of rdxA mutations. Moreover, mutations in rpsU may play a role in metronidazole resistance.